PENGARUH JUMLAH PENDUDUK, PENGANGGURAN, DAN PENDIDIKAN TERHADAP KEMISKINAN MASYARAKAT DI PROVINSI BALI - Riestiawan, Gede Surya; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
The purpose of this study was to determine the effect of population, unemployment and education on poverty levels in the Province of Bali 2019-2021. The research method used in this research is descriptive quantitative method. Types and sources of research data used are secondary data, which are obtained directly from the object being examined. Processing the data using SPSS.The results of this study indicate that partially the effect of population, unemployment, and education on the poverty rate of people in the Province of Bali in 2019 to 2021 it was found that the variable population growth has a positive and significant effect on the level of poverty that occurs in the Province of Bali, while the variable  Unemployment and education do not necessarily increase poverty.  Total Population, Total Unemployment and Education simultaneously or together have a positive influence on Poverty in the Province of Bali, while the Coefficient of Determination shows that Total Population, Total Unemployment and Education have an effect of 35.1% to influence the Poverty variable in Bali Province and the remaining 64  .9% is influenced by other factors or other variables outside this research model.   Keywords: poverty, total population, unemployment, education